Recovering Risky Technologies Using The Almost Ideal Demand System: An Application To U.S. Banking - Joseph P. Hughes; Loretta J. Mester; William Lang; Choon-Geol Moon (Rutgers University, Department of Economics, 2000)
We argue for a shift in the focus of modeling production from the traditional assumptions of profit maximization and cost minimization to a more general assumption of managerial utility maximization that can incorporate risk incentives into the analysis of production and recover value-maximizing technologies. We show how this shift can be implemented using the Almost Ideal Demand System. In addition, we suggest a more general way of measuring efficiency that can incorporate a concern for the market value of firms' assets and equity and identify value-maximizing firms. This shift in focus bridges the gap between the risk-incentives literature in banking that ignores the microeconomics of production and the production literature that ignores the relationship between production decisions and risk.
Keywords: D20; D21; G21; 330; agency problems; banking; efficiency; production; risk